Motivasi Kerja dan Komitmen Organisasi: Studi Kualitatif tentang Pengalaman Karyawan - Putra, Firdaus (Yayasan Aya Sophia Indonesia, 2026)
Low employee commitment remains a critical challenge in human resource management across various organizations. This study aims to explore how employees perceive work motivation and how these perceptions shape organizational commitment from the perspective of employee experiences. A qualitative descriptive approach was employed, involving active employees as research participants. Data were collected through in-depth interviews and document analysis. The data were analyzed using thematic analysis, supported by source triangulation to ensure credibility. The findings reveal that work motivation is perceived as a personal and dynamic drive shaped by a combination of intrinsic and extrinsic factors. Intrinsic motivation, including meaningful work, recognition, and opportunities for personal development, plays a dominant role in fostering affective organizational commitment. In contrast, extrinsic motivation tends to produce more pragmatic and short-term forms of commitment. These results highlight the importance of managing meaningful work experiences to strengthen sustainable organizational commitment.